2010
DOI: 10.1073/pnas.1003909107
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy induces a fetal antigen-specific maternal T regulatory cell response that contributes to tolerance

Abstract: A fetus is inherently antigenic to its mother and yet is not rejected. The T regulatory (Treg) subset of CD4 + T cells can limit immune responses and has been implicated in maternal tolerance of the fetus. Using virgin inbred mice undergoing a first syngenic pregnancy, in which only the male fetuses are antigenic, we demonstrate a maternal splenocyte proliferative response to the CD4 + T cell restricted epitope of the male antigen (H-Y) in proportion to the fetal antigen load. A portion of the maternal immune … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
204
1
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 215 publications
(216 citation statements)
references
References 23 publications
10
204
1
1
Order By: Relevance
“…Maternal Tregs have been studied in the context of healthy and pathologic pregnancies 2, 4, 5, 35. In contrast, very little is known about a potential role of fetal Tregs in pregnancy disorders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Maternal Tregs have been studied in the context of healthy and pathologic pregnancies 2, 4, 5, 35. In contrast, very little is known about a potential role of fetal Tregs in pregnancy disorders.…”
Section: Discussionmentioning
confidence: 99%
“…To cope with these significant antigenic differences, mechanisms of immune tolerance are invoked during pregnancy 2, 4, 5. Among these are the actions of the powerful T regulatory (Treg) cell that has the ability to negatively regulate major portions of the cellular immune system 6.…”
Section: Introductionmentioning
confidence: 99%
“…However, establishment of fetomaternal tolerance itself, reflected by reproductive success, did not depend on the presence of GR in T cells. Although Treg-driven tolerance has been shown to be fetal antigen specific in the first place (22), it has also been noted that Tregs are able to suppress T-cell responses to unrelated antigens in the form of a bystander suppression (50). This can have detrimental consequences as Treg expansion leaves pregnant mice more prone to infections with certain pathogens including Listeria and Salmonella species, whereas Treg depletion has been shown to restore host defense (23).…”
Section: Discussionmentioning
confidence: 99%
“…Although elegant studies in mice have shown the presence of maternal T cells specific for paternal transgenes (i.e., actin-OVA and actin-2W1S; refs. 20, 21) or for male antigens (22), the nature of the tissue targeted by maternal effector T cells cannot be defined, since the paternally inherited genes are assumed to be present in both trophoblast cells and fetus. In humans, trophoblast-specific T cells are likely to be HLA-C restricted, as this is the only polymorphic trophoblast HLA class I molecule.…”
Section: T Cells In Pregnancymentioning
confidence: 99%